KALENDER SEJARAH INDONESIA (LENSA): ALTERNATIF MEDIA PEMBELAJARAN SEJARAH YANG SOLUTIF - Mukrim, Ahmad; Faradiva, Nadilla; Nuri, Ilham; Septiawan, Indra (Program Kreativitas Mahasiswa - Karsa Cipta, 2013)
Kalender Sejarah Indonesia (LENSA) is an alternative media of history learning by using daily calendar which is featured by Indonesia history explanation that occurred at the date with wisdom quotes. LENSA has two models, there is print and virtual models. Specifically, this media is the history material that presented attractively and easy to understand. After field trials and launching, LENSA can be an alternative solution as learning media of Indonesia history. It means that this learning media can help students understand the history of Indonesia. Teachers have to deliver subject material, and increasing knowledge about Indonesia history for society.